2006
DOI: 10.1080/01460860601115130
|View full text |Cite
|
Sign up to set email alerts
|

Looking at Families in Nursing Research: Strategies for Study Design

Abstract: Pediatric nurses have identified the importance of studying children within the context of their families. There have been calls for attention to the family as the focus of study and unit of analysis in nursing research. One of the most important strategies for designing a study that keeps the focus on the family is the maintenance of study integrity. All the strategic choices made by the researcher when developing the research design need to reflect the theoretical premises on which the study is built. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Family functioning is characterized by the overall health and pathology of the family system, encompassing six dimensions: problem solving, communication, roles, affective responsiveness, affective involvement, and behavior control [23]. In this study, family was conceptualized as “A self-identified group of two or more individuals…who function in a way that they consider themselves to be a family” [32]. Participants self-defined family and were asked to complete this instrument by using whoever they considered to be family .…”
Section: Methodsmentioning
confidence: 99%
“…Family functioning is characterized by the overall health and pathology of the family system, encompassing six dimensions: problem solving, communication, roles, affective responsiveness, affective involvement, and behavior control [23]. In this study, family was conceptualized as “A self-identified group of two or more individuals…who function in a way that they consider themselves to be a family” [32]. Participants self-defined family and were asked to complete this instrument by using whoever they considered to be family .…”
Section: Methodsmentioning
confidence: 99%
“…This type of analysis is important when considering the shared experiences of the respondents that when considered jointly may have significant effects on the outcome variable of interest. Structural equation modeling was used to answer the research question because it allows for exploration of relationships and inter-relationships between variables and is an especially useful approach to analyzing dyadic data (Kenny et al, 2006; Marcellus, 2006). SEM was used to explore the effects of asthma knowledge, self-efficacy to manage asthma, and asthma management on the child’s QOL…”
Section: Study Proceduresmentioning
confidence: 99%
“…While many studies have been conducted to improve parents’ and children’s management of this complex condition, they fail to capture the work that is shared by the parent-child dyad (Marcellus, 2006). In many studies of childhood chronic illness a single respondent, usually the parental caregiver, provides all the data for the family.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For Marcellus, 8 the study of families represents a methodological challenge that studies in individuals do not have. Family researchers try to ensure that the unit of analysis reflects the family as such, in other words, they try to correctly choose the family member who will answer the study questions.…”
Section: Introductionmentioning
confidence: 99%